The United States and World War II : the awakening giant - Folly, Martin H., 1957-; British Association for American Studies (Edinburgh : Edinburgh University Press, 2002)
"Coverage is broad-ranging - the narrative begins in the late 1930s, demonstrating that an understanding of World War II as a transforming event requires discussion of the prior state of affairs, and ends with a consideration of the legacy of the war and its continuing significance. Overall, this book provides an introduction to all aspects of the American experience of World War II."--Jacket
Preface -- List of abbreviations and codenames used -- Select chronology of World War II -- Maps -- 1. A nation unprepared -- 2. Setbacks and struggles -- 3. Awakening the sleeping giant -- 4. A nation triumphant -- 5. The problems of victory -- 6. The United States and World War II -- Select bibliography -- Index.
Includes bibliographical references (pages 159-170) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: World War, 1939-1945 -- United States; United States -- History -- 1933-1945.; Guerre mondiale, 1939-1945 -- États-Unis.; États-Unis -- Histoire -- 1933-1945.; HISTORY -- Military -- World War II; United States; Weltkrieg; USA; 1933-1945; History